2012
DOI: 10.1080/17461391.2011.641033
|View full text |Cite
|
Sign up to set email alerts
|

European athletes dominate performances in Double Iron ultra‐triathlons – A retrospective data analysis from 1985 to 2010

Abstract: We investigated the participation and performance trends of ultra-endurance triathletes from all nationalities competing in a Double Iron ultra-triathlon (7.6-km swim, 360-km cycle and 84.4-km run) from 1985 to 2010. A total of 1854 athletes participated in 92 Double Iron ultra-triathlons. The majority of the winners came from Europe with 72 victories, followed by North America with 17 victories. The race time for the European ultra-triathletes was 1340 (s=95.3) min, decreasing highly significantly (r 2=0.28; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 43 publications
0
40
0
Order By: Relevance
“…[3] Ultra-triathlons, consisting of distances greater than Ironman distance include double Ironman triathlons (7.6km swim, 360km cycle and 84 km run) and decaIronman triathlon (38km swim, 1800km cycle and 420 km run) also appeared during the 1980"s with the first double Ironman triathlon held in 1985 in Huntsville (USA). [4,5,6,7] More recently, in addition to conventional road based triathlon, off-road triathlon combining swimming, mountain biking and trail running has also established itself in the field of endurance sports, and has grown very rapidly in popularity. [8,9] Triathlon performance has been studied from numerous perspectives by a number of research groups over approximately the same period that the sport has grown.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Ultra-triathlons, consisting of distances greater than Ironman distance include double Ironman triathlons (7.6km swim, 360km cycle and 84 km run) and decaIronman triathlon (38km swim, 1800km cycle and 420 km run) also appeared during the 1980"s with the first double Ironman triathlon held in 1985 in Huntsville (USA). [4,5,6,7] More recently, in addition to conventional road based triathlon, off-road triathlon combining swimming, mountain biking and trail running has also established itself in the field of endurance sports, and has grown very rapidly in popularity. [8,9] Triathlon performance has been studied from numerous perspectives by a number of research groups over approximately the same period that the sport has grown.…”
Section: Introductionmentioning
confidence: 99%
“…Athletes require special characteristics in anthropometry (Hoffman, 2008 Besides the aspects of training and race preparation, characteristics of both anthropometry and physiology as well as the nationality of an athlete could also have an influence on the outcome of the performance in an endurance race (Larsen, 2003;Lepers et al, 2011;Rüst et al, 2012b). Regarding the origin of runners, Larsen (2003) reported that in the last two decades a change in the dominance of middle and long-distance running events occurred.…”
Section: Introductionmentioning
confidence: 99%
“…The Double Iron ultra-triathlon covers 7.6km swimming, 360km cycling, and 84.4km running. This first ultra-triathlon was held in the United States with 23 athletes (Rüst, Knechtle, Knechtle, Lepers, & Rosemann 2012). Then, in 1988, the first Triple Iron ultra-triathlon covering 11.6km swimming, 540km cycling, and 126.6km running was organized in Le Fontanil, France, with 11 starters.…”
Section: Introductionmentioning
confidence: 99%
“…investigated in a very recent study where Rüst, Knechtle, Knechtle, Lepers, and Rosemann (2012) reported European dominance in Double Iron ultra-triathlons worldwide.…”
Section: Introductionmentioning
confidence: 99%